2019
DOI: 10.1093/petrology/egz007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Melt Infiltration on Metagranitic Rocks: the Snieznik Dome, Bohemian Massif

Abstract: Highly deformed banded phengite-biotite metagranite from the Snieznik dome in the Bohemian Massif has been modified locally to have stromatic, schlieren or nebulitic textures typical of migmatites. This occurred mostly along subvertical deformation zones at eclogitefacies conditions, at a scale of several centimetres to several metres, mostly parallel to the foliation. The transition from banded to migmatite types of orthogneiss is marked by an increase in the amount of phases interstitial along grain boundari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 95 publications
(130 reference statements)
0
10
0
Order By: Relevance
“…In order to put valorisation to the field observations, we make here some basic interpretation of the observed textural transitions (for similar interpretation see Hasalová et al 2008a,b,c;Schulmann et al 2008;Chopin et al 2012b;Štípská et al 2019). From the gradual transitions of the rock types in the field, it is concluded that the banded type II, schlieren and nebulitic orthogneiss types resulted from progressive disappearance of the originally monomineral augen/banded texture typical of the augen/banded type I orthogneiss.…”
Section: Field Relations and Structural Evolutionmentioning
confidence: 79%
See 4 more Smart Citations
“…In order to put valorisation to the field observations, we make here some basic interpretation of the observed textural transitions (for similar interpretation see Hasalová et al 2008a,b,c;Schulmann et al 2008;Chopin et al 2012b;Štípská et al 2019). From the gradual transitions of the rock types in the field, it is concluded that the banded type II, schlieren and nebulitic orthogneiss types resulted from progressive disappearance of the originally monomineral augen/banded texture typical of the augen/banded type I orthogneiss.…”
Section: Field Relations and Structural Evolutionmentioning
confidence: 79%
“…From the observed textural gradients occurring parallel to the S2 foliation and ranging from the banded type II to schlieren and nebulitic orthogneiss types, it is concluded that these transformations occurred mainly during the D2 deformation. As the schlieren and nebulitic textures are commonly assigned to migmatites (Mehnert, 1971), it is supposed that the observed textural transitions are a result of transformation under the presence of melt (for similar interpretation see also Hasalová et al 2008a,b,c;Schulmann et al 2008;Chopin et al 2012b;Závada et al 2018;Štípská et al 2019).…”
Section: Field Relations and Structural Evolutionmentioning
confidence: 89%
See 3 more Smart Citations